Fitness tests and match performance in a male ice hockey national league - Haugen, T.; Hopkins, W.; Breitschädel, F.; Paulsen, G.; Solberg, P. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine if generic off-ice physical fitness tests can provide useful predictions of ice hockey players` match performance.